Structural Optimization of Mechanical Systems - Topology optimization with parametrization of hardpoint positions - Berndtsson, Aliki; Mattiasson, Andreas (My University, 2019)
This is the report for a master’s thesis project on structural optimization of mechanical systems, at Volvo Cars. The shift towards electric propulsion and high cost of battery capacity puts further need for lightweighting since it can bring significant cost advantages in terms of price per range. Topology Optimization (TO) is a method that finds its true potential in context with additive manufacturing due to high level of design freedom, but it can also be beneficial in context with other manufacturing techniques such as casting. Previous thesis projects at Volvo Cars have emphasized TO in the context of casted components and it is widely used today. However, TO is often used to refine the geometry relatively late and applied to single components with predetermined boundary conditions such as joint loads and joint positions, i.e. constraints that narrows the solution space. The main idea for this project is therefore to broaden the solution space by introducing TO on system level together with an outer parametric loop for joint positions. This method can be applied to mechanical systems in general, but the main focus is to provide a prestudy for applications within automotive wheel suspension systems. A Finite Element (FE) model of a rear wheel suspension system is developed and validated with respect to force signals from an existing, dynamic, full vehicle model. The linkages are then optimized with respect to stiffness and weight based on current joint positions. The proposed scheme for parametrization of joint positions is limited to a two-component system. Over all, the FE-model correlates well with respect to force signals, but there are still room for improvements, especially with respect to modeling of dampers. In order to introduce proper stiffness constraints during optimization, there is also a need for correlation of the FE-model with respect to displacements. The future potential for TO on system level seems promising. In addition to a broader solution space through parametrization of joint positions the relative mass distribution between different components are treated within one single system optimization.
Keywords: Structural optimization of a multibody systems; Topology optimization; Parametrization of joint positions